Unmet care needs of the oldest old with late-life depression: a comparison of patient, caring relative and general practitioner perceptions : results of the AgeMooDe study - Stein, Janine; Weyerer, Siegfried (Journal of affective disorders, 2016)
Background - Research showed that the perception of unmet needs may differ between patients, caregivers and professionals. Lacking agreement with regard to unmet needs between raters involved may have a negative impact on treatment of late-life depression. - Methods - As part of the multicenter German study “Late-life depression in primary care: needs, health care utilization and costs” (AgeMooDe), n=1188 primary care patients aged 75-98 with and without depression, relatives (n=366) and general practitioners (GPs, n=1152) were assessed using the German version of the Camberwell Assessment of Need for the Elderly (CANE) in order to identify patients' unmet needs from different perspectives. Kappa coefficients were computed to determine level of agreement between perspectives. Penalized likelihood logistic regression models were run in order to assess the association between depression severity and disagreement between perspectives with regard to unmet needs. - Results - The prevalence of unmet needs was higher in depressive patients. Kappa coefficients were on average higher for depressive patients ranging from poor to substantial. Severity of depression was significantly associated with disagreement regarding unmet needs between perspectives. - Limitations - The cross-sectional design of the study limits the results. Only a part of caring relatives was able to participate. - Conclusions - Perceptions of unmet needs in the oldest old primary care patients suffering from depression strongly differ between raters. Severity of depression seems to exacerbate the discrepancy between involved perspectives. The negative impact that depression severity may have on the perception and assessment of unmet needs requires greater attention by GPs.